Promotion Mix Implementation In Accommodation Businesses In The Pandemic Time Covid-19 - Marini, Sri; Aprilia, Lu'luwatin Rosdiana; Faot, Alvina Marni Theola (Politeknik Pariwisata NHI Bandung, 2021)
The covid 19 outbreak is not only detrimental in health, but also has an impact on the community's economic sector. Tourism and hospitality are the sector that feels the most impact. They lost domestic tourists, as well as foreign tourists. The accommodation businesses were the ones that experienced the most revenue declines, even 40,000 hotel room cancellations occurred with a total loss of Rp. 1 trillion. Hotel occupancy rates will continue to erode along with the enactment of social restrictions. The hotels work hard in designing the right strategy to adapt to the current conditions, so as to increase the volume of room sales. Marketing management is a strategy for selecting target markets and gaining, retaining and growing customers by creating, delivering and communicating superior customer value. Promotional are one part of the marketing mix that is used to introduce and inform potential guests or consumers about the products and services offered. Implementation can be done in the promotion mix through broadcasting, sales promotion, personal selling, public relations and direct marketing. This study aims to determine the effectiveness of the implementation of the promotion mix on accommodation businesses during the covid 19 pandemic. The research method used is a descriptive research method with a quantitative approach. The population are tourists who visit V Hotel & Residence Bandung whilea non-probability random sampling technique used in this study with total sample of 110 respondents. SPSS was used to analyze the questionnaire data. The results showed that advertising as an effective marketing mix was implemented in accommodation businesses during the covid 19 pandemic. Advertising using electronic media and the internet had an impact of 59.6%. Promotional mix through the internet using social media would be best to avoid a promotional mix that uses too large a fee.